Dzieje archiwum Akademii Ekonomicznej we Wrocławiu w latach 1947-2007. Rola i zadania - Grzelak, Elżbieta (The History of The Wrocław University of Economics Archive (1947-2007). The Role and The Tasks, 2008)
Over the last several decades, the archive of the Wrocław University of Economics has been undergoing changes in its meaning: from the place associated with the room for gathering needless acts to the place intended for being storehouse of knowledge on different science topics afforded through critical analysis of archival materials. The School Archive has completed the basic tasks of collecting, preserving, describing, classifying and providing access to archival materials, especially for research purposes. The quality of such transformation can be estimated by visible improvement of material base as well as technical equipment, structural changes in the section, quick growth of documentation number connected with adaptation of past boiler room for archive purpose. Apart from it - attaching importance to making accurate act's description.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 26, s. 176-185